Managing Food Price Inflation in South Asia - Ahmed, Sadiq; Jansen, Hans G.P. (Dhaka: The University Press Limited, 2013)
The surge in global commodity prices of the past few years has presented a tremendous development challenge to South Asian countries. On a net basis South Asia is estimated to have suffered an income loss equivalent to some 9.6 percent of Gross Domestic Product (GDP) between January 2003 and April 2008. Although much of the income loss resulted from the hike in petroleum prices, the surge in food prices between January 2007 and April 2008, especially of staple food ? wheat and rice ? has created tremendous adverse social impact in South Asia. All countries have witnessed unprecedented surge in food prices, although India was able to limit this increase owing to good harvests and timely interventions using stock management and public food distribution. Net food importing countries like Afghanistan, Sri Lanka and Bangladesh have suffered the most from the food price crisis. The emerging global financial crisis is adding fuel to the fire, with expected future adverse consequences for macroeconomic balances and growth.